Do enzyme inhibitors dicyandiamide and NBPT influence the microbial immobilization of phosphorus in Humic Cambisol? - Daniel J. Dall’Orsoletta; Luciano C. Gatiboni; Djalma E. Schmitt; Bruna Arruda; Joice C. Heidemann (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The application of nitrogen fertilizers, both organic and mineral, can cause nitrate losses by leaching. To minimize this effect, enzyme inhibitors are used. However, the effects on microbial biomass, which is the most sensitive and dynamic compartment of nutrients in the soil, as well as its effect on nutrients such as phosphorus (P) are unknown. This study aimed to evaluate the influence of the enzyme inhibitor (EI) on soil microbial phosphorus (Pm) when mineral fertilizer (NPK) or liquid swine manure (LSM) was applied in corn cultivation. The experiment was installed in a Humic Cambisol in Lages – SC, Brazil (27° 47’ 08” S; 50° 18’ 09” W) in the 2012/2013 season. The treatments consisted of: i) NPK; ii) NPK + EI; iii) LSM; iv) LSM + EI, applied before sowing of corn, and v) control (without application of fertilizer and enzyme inhibitor) arranged in a randomized block design, under no-tillage system. Soil samples were collected from the 0-0.10 m layer at 0, 10, 25, 58, 90, 135 and 202 days after application of the treatments. The Pm content was not affected by the enzyme inhibitor application but was influenced throughout the crop cycle in response to water balance and corn cultivation.